(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Solar power plants (PLTS) are one of the renewable energy solutions that are increasingly popular around the world. By utilizing solar radiation as the main energy source, solar PV is able to generate electricity through the photovoltaic conversion process or centralized solar power system. Photovoltaic technology uses solar cells to convert direct sunlight into electricity. This Community Service (PKM) discusses "Installation of Solar Power Plants (PLTS) as a Source of Water Pump Energy to Provide Clean Water in the Puncak Labuang Ecotourism Destination". The purpose of this PKM is to help residents around the peak of Labuang get a supply of clean water. This PKM uses a Solar Panel with a capacity of 120 WP and 2 12V DC water pumps with a total power of 52 W installed in series, where after testing, the water pump can drain water from a height of 7 m and is able to fill a water tank with a volume of 520 L within 67 minutes. Furthermore, this solar power plant is also able to produce a maximum power of 98 Watts, a current of 7.2 Ampere. This solar power plant is able to produce a maximum of 446 Wh of energy that can be stored in the battery. With a power reserve in the battery, this system is able to fill the water tank at night as many as 8 times from an empty condition if there is a lot of need due to camping activities etc. — Pembangkit listrik tenaga surya (PLTS) kini menjadi salah satu alternatif energi terbarukan yang kian diminati secara global. Melalui pemanfaatan cahaya matahari sebagai energi utama, PLTS menghasilkan listrik dengan menggunakan teknologi fotovoltaik atau sistem tenaga surya terfokus. Melalui sel surya, teknologi fotovoltaik dapat langsung mengubah energi cahaya matahari menjadi energi listrik. Kegiatan Pengabdian kepada Masyarakat (PKM) ini berfokus pada “Instalasi Pembangkit Listrik Tenaga Surya (PLTS) sebagai Sumber Energi bagi Pompa Air dalam Penyediaan Air Bersih di Kawasan Ekowisata Puncak Labuang”. Tujuan utama dari kegiatan ini adalah untuk mendukung masyarakat di sekitar kawasan Puncak Labuang dalam memperoleh akses terhadap air bersih. PKM ini menggunakan Panel Surya berkapasitas 120 WP dan 2 buah pompa air 12V DC dengan total daya 52 W yang dipasang secara seri, dimana setelah dilakukan pengujian, pompa air dapat mengalirkan air dari ketinggian 7 m dan mampu mengisi tangki air dengan volume 520 L dalam waktu 67 menit. Selanjutnya PLTS ini juga mampu menghasilkan daya maksimal 98 Watt, arus yang mencapai 7,2 Ampere. PLTS ini mampu menghasilkan maksimal energi 446 Wh yang dapat disimpan didalam baterai. Dengan Cadangan listrik didalam baterai, sistem ini mampu mengisi tangki air di malam hari sebanyak 8 kali dari kondisi kosong jika ada kebutuhan yang banyak karena aktivitas kemah dll.